Durio: A bibliographic review - Brown, M.J.; International Plant Genetic Resources Institute (1997)
Among the native tropical underutilized fruits of promising potential, durian assumes great importance particularly in Malaysia, Thailand and Indonesia. Global interest in this fruit is catching up fast and its commercial prospects increasing. With promising clones now available and considering the export potential of durian, more area under its cultivation has led to loss of primitive diversity and wild/semi-wild/domesticated species. Further, research and development efforts are still required to understand durian flora1 biology and physiology of fruit set, and assessing wild and domesticated primitive genepools for their usefulness in diseases/pest resistance, physiological stress and other attributes imparting better characteristics. Specific treatises dealing with studies on taxonomy, genetic diversity, flora1 biology, breeding, improvement, conservation and utilization aspects are wanting. In the above context, the detailed synthesis provided on durian by Dr. Michael J. Brown is welcomed. It is perhaps for the first time that such a comprehensive account has been attempted on an underutilized fruit crop genepool. This publication on Durian which is a review of bibliography of about 1000 references, provides a well-synthesized information on different aspects of Durio. It deals with its origin, history, taxonomy of wild and cultivated species, identification, morphology of flower and fruit and other organs, its edibility, composition and uses, nutritional aspects, medicinal and toxicological prospects, seed physiology, pollination biology, ecology, forest resources, crop improvement efforts, agronomic requirements, propagation, cultivation and maintenance, post harvest technology, genetic resource and conservation.